2010
DOI: 10.3389/fnhum.2010.00188
|View full text |Cite
|
Sign up to set email alerts
|

Early neural markers of implicit attitudes: N170 modulated by intergroup and evaluative contexts in IAT

Abstract: The Implicit Association Test (IAT) is the most popular measure to evaluate implicit attitudes. Nevertheless, its neural correlates are not yet fully understood. We examined event related potentials (ERPs) in response to face- and word processing while indigenous and non-indigenous participants performed an IAT displaying faces (ingroup and outgroup members) and words (positive and negative valence) as targets of category judgments. The N170 component was modulated by valence of words and by ingroup/outgroup f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 97 publications
5
39
2
2
Order By: Relevance
“…The second was found in a later mental process, starting around 450 ms after stimulus onset (microstate 6). Thus, in line with previous EEG studies, we found differences between the two IAT conditions in both the first (18)(19)(20)(21) and second half (18,19,(22)(23)(24) of task execution. Adding to previous research, we demonstrated that these differences were due to a longer duration of the same mental Congruent 0 88 88 132 158 224 224 252 252 442 442 612 612 742 742 868 Incongruent 0 88 88 132 156 226 226 260 260 446 446 664 664 826 826 954 processes in the incongruent condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The second was found in a later mental process, starting around 450 ms after stimulus onset (microstate 6). Thus, in line with previous EEG studies, we found differences between the two IAT conditions in both the first (18)(19)(20)(21) and second half (18,19,(22)(23)(24) of task execution. Adding to previous research, we demonstrated that these differences were due to a longer duration of the same mental Congruent 0 88 88 132 158 224 224 252 252 442 442 612 612 742 742 868 Incongruent 0 88 88 132 156 226 226 260 260 446 446 664 664 826 826 954 processes in the incongruent condition.…”
Section: Discussionsupporting
confidence: 92%
“…[18][19][20][21] and at late time periods (in the second half of task execution; refs. 18, 19, and 22-24).…”
Section: Significancementioning
confidence: 99%
“…This finding is consistent with previous electrophysiological studies on implicit self-evaluation, which also failed to find the compatibility effect on perceptual process (e.g., Egenolf et al, 2013;Yang & Zhang, 2009). However, it is inconsistent with some previous studies on implicit attitudes (e.g., racial attitude), which found that perceptual process was affected by racial biases (e.g., Ibanez et al, 2010). In our opinion, this inconsistency is due to the difference between self-evaluation and ingroup/outgroup evaluation.…”
Section: Discussioncontrasting
confidence: 80%
“…First, visual perceptual processes are sensitive to compatibility, reflected in the occipital distributed P100 (Fleischhauer, Strobel, Diers, & Enge, 2014) and N170 (Ibanez et al, 2010) components. Second, the N200 was found to be sensitive to the category-attribute association in the IAT paradigm (Coates & Campbell, 2010).…”
mentioning
confidence: 99%
“…The Emotion Recognition Task (ERT) is a face and word recognition task adapted from previous studies (Hurtado et al, 2009; Ibáñez et al, 2010, 2011; Petroni et al, 2011). This cognitive function has been thought of as a building block of social cognition (Green et al, 2008; Kurtz and Richardson, 2011; Pinkham et al, 2014).…”
Section: Methodsmentioning
confidence: 99%